Hydrogen sulfide and ferroptosis inhibition underlies the dietary restriction-induced protection against cyclophosphamide cystitis - Mao, Zhimin; Chen, Ping; Ji, Qun; Zhao, Xiuling; Zhong, Kun; Zeng, Xuhui (Frontiers in Pharmacology, 2025)
Dietary restriction (DR) has emerged as a potential therapeutic intervention for various pathological conditions. This study investigated the effects of DR on cyclophosphamide-induced cystitis in mice. Animals were subjected to controlled food restriction for 1 week prior to cyclophosphamide administration. We evaluated changes in body weight, bladder pathology, redox status, and ferroptotic parameters. DR significantly attenuated cyclophosphamide-induced cystitis severity, as evidenced by reduced bladder weight, decreased lipid peroxidation, and diminished ferroptotic markers in bladder tissue. Mechanistic investigations revealed that DR upregulated hepatic hydrogen sulfide (H2S)-synthesizing enzymes and enhanced H2S production. Inhibition of H2S-synthesizing enzymes with DL-propargylglycine (PAG) and aminooxyacetic acid (AOAA) exacerbated cyclophosphamide-induced cystitis, whereas administration of diallyl trisulfide (DATS), an H2S donor, markedly ameliorated bladder pathology. In vitro studies demonstrated that H2S donors, NaHS and DATS, protected against cyclophosphamide metabolite acrolein (ACR)-induced urothelial cell death by suppressing oxidative stress, as indicated by reduced p38 MAPK activation and protein carbonylation. These findings suggest that DR confers protection against cyclophosphamide-induced cystitis through the induction of endogenous H2S production and inhibition of ferroptosis. Our study provides additional evidence supporting the health-promoting effects of DR as well as novel mechanistic insights into the beneficial effects of DR. Given H2S has anti-inflammatory and anti-oxidative properties and that oxidative stress and ferroptosis underlie various diseases, our finding could have broader implications.